Design of a probe excited circular ring above the reflector for bridging outdoor wireless LAN applications - Phongcharoenpanich, Chuwong; Rattanachote, Ittiphol; Wounchoum, Phairote; Kosulvit, Sompol; Krairiksh, Monai (My University, 2003)
A high gain undirectional antenna using a probe excited circular ring above the circular reflector is presented. This structure is proposed for installation as a bridging outdoors for wireless LAN system. The structure of the antenna is compact and the cost is low. The design is simple and straightforward. The matching condition between the antenna and the transmission line is achieved. This antenna structure is very useful for application in the wireless LAN system.